Who Cares? Attitudes Towards Redistribution and Fiscal Austerity - Sarah Brown; Alexandros Kontonikas; Alberto Montagnoli; Mirko Moro; Dafni Papoutsaki; Willem Sas (Center for Economic Studies and ifo Institute (CESifo), 2021)
We present new evidence showing that fiscal austerity strengthens support for redistribution, especially for the relatively well-off. Our theoretical model proposes two mechanisms to explain this heterogeneity in support for redistribution: `altruism' and `appreciation'. We test our theoretical model's predictions by matching attitudes reported in the British Social Attitudes Survey with local area-level spending cuts in England over the period 2010 to 2015. We exploit the spatial and temporal variation in spending cuts at the Local Authority level to compute a plausibly exogenous measure of the austerity shock. We find evidence for these two channels.
Keywords: D30; D64; E62; H20; H30; H60; 330; austerity; fiscal consolidation; fiscal policy; redistribution; political attitudes; altruism; appreciation